(untitled) (Journal of the College of Basic Education, 2022)
Psychological unity is one of the most important threads that ran a lot of self-modern and education scientists today to be considered a psychological crisis experienced by the man under the weight of the daily problems faced by, the psychological unity is painful psychological experience has been suffering from an individual even if it is between his family and his friends when the free life of relations social intimacy and affection as a result of individual’s sense of lack of acceptance and love and attention from the other side, they are in all cases are found in all stages of life, as research aims to identify the unit and its relationship with some personal characteristics of the students of the Faculty of Physical Education and Sports Sciences - Baghdad University level, and I suppose researchers a correlation between mental unity and some personality traits relationship, and that the methodology used is descriptive method survey manner for suitability nature of the research problem, as it was determined the research community students College of Physical Education and Sports Science - University of Baghdad, as the researchers chose to sample randomly totaling (22 ) students, and researchers used intelligence Freiburg for personal and psychological unity scale as a research tool, and important conclusions they reached that students who were of the limits of the center in most of the personality traits in question except feature (the ability arousal), and recommendations researchers need to focus on the personal aspects by developing personal attributes when rehabilitation and teaching students and the need for the presence of a psychologist